2023
DOI: 10.3389/fmicb.2023.1105675
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the role of the milk microbiome in mastitis in the multi-omics era

Abstract: There is growing interest in a functional understanding of milk-associated microbiota as there is ample evidence that host-associated microbial communities play an active role in host health and phenotype. Mastitis, characterized by painful inflammation of the mammary gland, is prevalent among lactating humans and agricultural animals and is associated with significant clinical and economic consequences. The etiology of mastitis is complex and polymicrobial and correlative studies have indicated alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“… 2020 ; Couvillion et al. 2023 ). Recently, it was reported that fecal microbiota transplantation led to dysfunctional microbiota in the gut as well as caused mastitis in animal models (Ma et al.…”
Section: Mastitis Immunotherapy and Other Strategiesmentioning
confidence: 99%
“… 2020 ; Couvillion et al. 2023 ). Recently, it was reported that fecal microbiota transplantation led to dysfunctional microbiota in the gut as well as caused mastitis in animal models (Ma et al.…”
Section: Mastitis Immunotherapy and Other Strategiesmentioning
confidence: 99%
“…social and reproductive behaviors) is well established (Archie & Tung 2015, Sarkar et al 2020, suggesting that a similar sharing of external microbes may occur between nursing mothers and neonates, regardless of milk production and consumption. In regards to maternal skin microbes colonizing mammary tissues and milk, bacteria have been shown to enter skin through a break or crack, usually on the nipple, and cause mastitis (Couvillion et al 2023). However, to our knowledge, no studies exist on the direct transfer of commensal skin bacteria to milk or breast tissue, and it remains unclear if microbial taxa can enter healthy nipple or areola tissue.…”
Section: Milk Microbiome Formationmentioning
confidence: 99%
“…Given the importance of diary production worldwide, milk microbiomes have received attention for their potential impact on the dairy industry's economic and global-health footprint. Numerous studies have reported on the milk microbial communities in healthy bovids compared to those with bovine mastitis, an infection of the mammary gland of significant economic concern for the dairy industry (Derakhshani et al 2018, Hoque et al 2020, Couvillion et al 2023. In multiple studies, increases in the abundance of specific milk microbes, namely Streptococcus and Staphylococcus species, have been correlated with mastitis (Lima et al 2017, Hoque et al 2019.…”
Section: Agricultural Animal Milk Microbiomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, bovine mastitis has been diagnosed in laboratories using culture-based microbiology methods, but these methods cannot detect low-abundant pathogens or co-infections in subclinical mastitis ( 7 ). With the rapid advancement of high-throughput next-generation sequencing (NGS) technology and bioinformatics pipelines, culture-independent techniques have exponentially grown in use over the last few years to overcome some inherent limitations of cultivation methods ( 8 , 9 ). This has become evident due to the increased number of studies concerning the bovine milk microbiome, especially based on targeted approaches such as metataxonomic analyses ( 10 13 ).…”
Section: Introductionmentioning
confidence: 99%